How service operations, perceived benefit, and psychological ownership enhance customer retention in retail - evidence in Vietnam supermarkets - Diep T.N. Nguyen; Minh Pham; Miloslava Chovancová; Sinh Duc hoang (Cogent Business & Management, 2023)
In a world with enormous opportunities and challenges from the 4.0 revolution and the lingering COVID-19 pandemic, customer retention is more important than ever for retailers. While marketing and advertising can be more or less limited during the pandemic, retailers pay more attention to the supply and service operations of products as salvage to satisfy the essential demands of customers. However, few scholars discuss the effects of service operations on customer retention in retail because it is lower consumer awareness and challenging to measure accurately and adequately. Therefore, with the foundation of commitment-trust theory, this study examines service operations' direct and indirect effects on customer retention through perceived benefit in omnichannel retailers. Simultaneously, it assesses how psychological ownership affects customer retention and moderates the effect of perceived benefit on customer retention in the Vietnamese supermarket as empirical evidence. The combination of a qualitative method (with 32 in-depth interviews) and a quantitative method (through a survey conducted with 374 shoppers) is implemented. Partial least-squares structural equation modelling with SmartPLS software is utilized for data analysis and hypothesis testing. From the findings, the study offers an operations perspective and a customer view of how to store service operations contribute to customer perception of benefits and customer retention. Interestingly, the study discovered that psychological ownership is not only a critical antecedent of customer retention but also enhances the effect of perceived benefit on customer retention as its moderating role.
Keywords: 650; Perceived benefit; psychological ownership; retailing; service-operations; supermarkets